Flexural Strength and Chloride Penetration Resistance of Reinforced Concrete Beam with Steel Fiber after Exposure to Chloride Environment with Cyclic Wetting and Drying - Sumranwanich, Taweechai; Prak, Lyna (Frontiers in Engineering Innovation Research, 2021)
This paper aims to study the flexural strength and chloride penetration resistance of reinforced concrete (RC) beam containing steel fiber after exposure to chloride environment with cyclic wetting and drying. The compressive and splitting tensile strengths of concrete containing steel fiber were also studied. Steel fiber was used at the content of 0.50% by volume of the concrete. Compressive and splitting tensile strengths and were tested at the age of 28 days. RC beams' flexural strength was tested after exposure to the cyclic wetting and drying period with 5.0% of chloride solution for two years. The chloride penetration of concrete was investigated. The study results found that the compressive strength of concrete containing steel fiber was similar to control concrete without steel fiber, but the splitting tensile strength of concrete mixed with steel fiber was higher than that without steel fiber. Considering the RC beam's flexural strength after exposure to cyclic wetting and drying, the RC beam's flexural strength with steel fiber was higher than the control RC beam without steel fiber. The RC beam's flexural strength exposed to the chloride environment was lower than that exposed to the water. Besides, RC beams with steel fiber had higher chloride penetration resistance than those without steel fiber.